2021
DOI: 10.7759/cureus.20714
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia With Systemic Lupus Erythematosus: Rare Association or Coincidence

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder due to autoantibodies directed against nuclear and cytoplasmic antigens that may affect several different organs. The association of SLE and acute myeloid leukemia (AML) is rare, the incidence of this combination is not known, but there are few case reports in the literature. We report here the case of a 62-year-old woman, admitted for aetiological diagnosis of weight loss and severe anemic syndrome. The blood count has objectified a pancytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Taguchi et al reported a case of APML developing in the course of SLE, highlighting the diagnostic challenge and the need for vigilance in monitoring patients with SLE for the development of hematologic malignancies [ 7 ]. Additionally, Tahri et al discussed a rare association between AML and SLE, emphasizing the need for further exploration of this topic [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taguchi et al reported a case of APML developing in the course of SLE, highlighting the diagnostic challenge and the need for vigilance in monitoring patients with SLE for the development of hematologic malignancies [ 7 ]. Additionally, Tahri et al discussed a rare association between AML and SLE, emphasizing the need for further exploration of this topic [ 8 ].…”
Section: Discussionmentioning
confidence: 99%